A genetically encoded toolkit of functionalized nanobodies against fluorescent proteins for visualizing and manipulating intracellular signalling - Prole, David L. (BMC Biol, 2019)
BACKGROUND: Intrabodies enable targeting of proteins in live cells, but generating specific intrabodies against the thousands of proteins in a proteome poses a challenge. We leverage the widespread availability of fluorescently labelled proteins to visualize and manipulate intracellular signalling pathways in live cells by using nanobodies targeting fluorescent protein tags. RESULTS: We generated a toolkit of plasmids encoding nanobodies against red and green fluorescent proteins (RFP and GFP variants), fused to functional modules. These include fluorescent sensors for visualization of Ca(2+), H(+) and ATP/ADP dynamics; oligomerising or heterodimerising modules that allow recruitment or sequestration of proteins and identification of membrane contact sites between organelles; SNAP tags that allow labelling with fluorescent dyes and targeted chromophore-assisted light inactivation; and nanobodies targeted to lumenal sub-compartments of the secretory pathway. We also developed two methods for crosslinking tagged proteins: a dimeric nanobody, and RFP-targeting and GFP-targeting nanobodies fused to complementary hetero-dimerizing domains. We show various applications of the toolkit and demonstrate, for example, that IP(3) receptors deliver Ca(2+) to the outer membrane of only a subset of mitochondria and that only one or two sites on a mitochondrion form membrane contacts with the plasma membrane. CONCLUSIONS: This toolkit greatly expands the utility of intrabodies and will enable a range of approaches for studying and manipulating cell signalling in live cells. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12915-019-0662-4) contains supplementary material, which is available to authorized users.